Planned near-total resection of large vestibular schwannoma for preservation of facial nerve function - M. Abdelmoez; Khaled Anbar; Ahmed M. Ali; Khalid Ma’moun Moenes Ibrahim; Hussein Fathalla (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Vestibular schwannoma (VS) is a prevalent cerebellopontine angle neoplasm, requiring microsurgical removal for complete eradication and preservation of the facial nerve for cochlear function. The aim of work is to evaluate the validity of near-total resection as an accepted surgical strategy in the management of large vestibular schwannomas regarding facial nerve function and good preservation. This is a prospective study conducted on twenty cases with KOOS grade 4 large vestibular schwannomas admitted to the neurosurgical department of Kasr El-Aini Hospital and underwent intended near-total resection of their lesions through the retrosigmoid approach. Results Results revealed that all patients had excellent facial nerve function House and Brackmann (HB) before operation. One month of follow-up after the operation, 8(40%) had facial nerve function HB-II, 9(45%) had H-III, and 3(15%) had HB-V. At the last clinical follow-up 6 month post-operative, 17 cases had good facial nerve function (including 7 cases with HB-I and 10 cases with H-II), 2 cases with fair facial nerve function (HB-III), and 1 case with poor facial nerve function (HB-V). Conclusions Near-total resection (NTR) can be considered as a successful treatment for large VS, preserving facial nerve function in 85% of cases and resecting over 90% of the initial tumor volume demonstrating its importance in the operative management of large vestibular schwannomas.